Associations between exposure to Information and Communication Technology (ICT) and reported discomfort among adolescents - Palmer, Kristy; Ciccarelli, Marina; Falkmer, Torbjorn; Parsons, Richard (IOS Press, 2013)
BACKGROUND: Use of Information and Communication Technologies (ICT) are common among adolescents in their daily activities.Exposure to ICT has been associated with discomfort and musculoskeletal disorders in adults, with growing concern about the potential risks to children and adolescents' physical health. OBJECTIVE: The objectives of this study were to (i) quantify self-reported discomfort and exposure to ICT among adolescents; and (ii) determine if associations exist between discomfort and levels of exposure.PARTICIPANTS: The participant group comprised 33 Australian adolescents aged 12–15 years. METHODS: The study used self-reports by participants for a one week period. Intensity and location of discomfort was reported via a written discomfort log. ICT exposure and physical activity were reported through an electronic time-use diary. RESULTS: The most common ICT types reported by participants were television, mobile phones and desktop and laptop computers. Discomfort was reported by 86% of participants. The most frequently reported areas were the legs, head/neck, back and shoulders. There was no statistical association found between ICT exposure and discomfort. The majority of participants exceeded the recommended 60 minutes per day of moderate to vigorous physical activity.CONCLUSIONS: High exposure to ICT and high prevalence of low level discomfort was reported by the participants. Participating in regular physical activity may have some protective effect against ICT-related discomfort.